Language attitudes and teacher training - Mamani Quispe, Luis (2012)
This paper relates linguistic attitudes and beliefs with the hypothesis of the implicit theories. Since this proposal would permit to explain how linguistic attitudes and beliefs are constituted in human beings, we would understand why linguistic discrimination persists. We propose that linguistic attitudes and beliefs are part of the implicit theories. Consequently, we suggest a set of linguistic notions that all professor might know to contribute to the eradication of linguistic discrimination.